2008
DOI: 10.1098/rspb.2008.1542
|View full text |Cite
|
Sign up to set email alerts
|

Voice pitch alters mate-choice-relevant perception in hunter–gatherers

Abstract: In humans, voice pitch is thought to be a cue of underlying quality and an important criterion for mate choice, but data from non-Western cultures have not been provided. Here we test attributions to and preferences for voices with raised and lowered pitch in hunter-gatherers. Using a forced-choice playback experiment, we found that both men and women viewed lower pitched voices in the opposite sex as being better at acquiring resources (e.g. hunting and gathering). While men preferred higher pitched women's v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
103
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 60 publications
(86 reference statements)
8
103
1
Order By: Relevance
“…Thus, any fitness-related benefits from mating with a relatively masculine male may trade off against the costs of their behavioural tendencies within a long-term relationship (Fink & Penton-Voak, 2002;Gangestad & Simpson, 2000). Consistent with this idea, women's preferences for male masculinity are modulated by a wide variety of factors, including menstrual cycle phase and hormone levels (e.g., Feinberg et al, 2006;Puts, 2005), hormonal contraceptive use , whether or not one is breastfeeding (Apicella & Feinberg, 2009), and indices of a women's own attractiveness (Vukovic et al, 2010;Vukovic et al, 2008).…”
mentioning
confidence: 52%
“…Thus, any fitness-related benefits from mating with a relatively masculine male may trade off against the costs of their behavioural tendencies within a long-term relationship (Fink & Penton-Voak, 2002;Gangestad & Simpson, 2000). Consistent with this idea, women's preferences for male masculinity are modulated by a wide variety of factors, including menstrual cycle phase and hormone levels (e.g., Feinberg et al, 2006;Puts, 2005), hormonal contraceptive use , whether or not one is breastfeeding (Apicella & Feinberg, 2009), and indices of a women's own attractiveness (Vukovic et al, 2010;Vukovic et al, 2008).…”
mentioning
confidence: 52%
“…Recent human studies have shown that the F0 of male speech influences male dominance attributions and may be important as a cue to the speaker's testosterone levels (Dabbs & Mallinger 1999;Evans et al 2008;Puts 2007). Moreover, human females find males with lower F0 more masculine and more attractive (Collins 2000;Feinberg et al 2005;Puts 2005), and in hunter-gatherer societies males with low F0 have higher reproductive success (Apicella et al 2006) and may be preferred as mating partners (Apicella & Feinberg 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Recent research has emphasized the importance of voice pitch for women's vocal attractiveness (e.g., APICELLA and FEINBERG 2009;COLLINS and MISSING 2003;FEINBERG et al 2005FEINBERG et al , 2008JONES et al 2008). For example, COLLINS andMISSING (2003) andFEINBERG et al (2008) reported positive correlations between voice pitch measurements taken from recordings of women's voices and attractiveness ratings of these voice recordings.…”
Section: Introductionmentioning
confidence: 99%
“…Vocal fundamental frequency, which is perceived as voice pitch, reflects the rate of vocal-fold vibration (TITZE 1994) and is negatively correlated with testosterone levels in men (TITZE 1994) and positively correlated with estrogen levels in women (ABITBOL et al 1999;FEINBERG et al 2006). Since cues of hormone levels are thought to be particularly important for attractiveness in humans (e.g., MILLER and TODD 1998), much of the research on human vocal attractiveness has investigated the relationship between voice pitch and attractiveness (APICELLA and FEINBERG 2009;COLLINS and MISSING 2003;FEINBERG et al 2005FEINBERG et al , 2008JONES et al 2008).…”
Section: Introductionmentioning
confidence: 99%